Odpowiedź :
a)
[tex] \frac{2}{3} + \frac{3}{4} = \frac{8}{12} + \frac{9}{12} = \frac{17}{12} = 1 \frac{5}{12} [/tex]
b)
[tex] \frac{3}{5} + \frac{4}{7} = \frac{21}{35} + \frac{20}{35} = \frac{41}{35} = 1 \frac{6}{35} [/tex]
c)
[tex] \frac{6}{8} - \frac{1}{5} = \frac{30}{40} - \frac{8}{40} = \frac{22}{40} = \frac{11}{20} [/tex]
d)
[tex] \frac{2}{3} - \frac{2}{4} = \frac{8}{12} - \frac{6}{12} = \frac{2}{12} = \frac{1}{6} [/tex]
e)
[tex] \frac{5}{9} + \frac{1}{2} = \frac{10}{18} + \frac{9}{18 } = \frac{19}{18} = 1 \frac{1}{18} [/tex]
f)
[tex] \frac{5}{7} + \frac{2}{3} = \frac{15}{21} + \frac{14}{21} = \frac{29}{21} = 1 \frac{8}{21} [/tex]
g)
[tex] \frac{4}{5} + \frac{4}{6} = \frac{24}{30} + \frac{20}{30} = \frac{44}{30} = 1 \frac{14}{30} = 1 \frac{7}{15} [/tex]
h)
[tex] \frac{4}{7} - \frac{1}{2} = \frac{8}{14} - \frac{7}{14} = \frac{1}{14} [/tex]
i)
[tex] \frac{2}{3} - \frac{2}{5} = \frac{10}{15} - \frac{6}{15} = \frac{4}{15} [/tex]
Myślę że pomogłem ;)